Stability and motion of foams and films in confined geometries - Drenckhan, Wiebke (Trinity College (Dublin, Ireland). School of Physics, 2005)
The last 20 years of research in the physics of foams display the development of a thorough understanding of dry and static foams. In the realm of wet and dynamic foams, however, many interesting and puzzling effects have been observed experimentally but lack theoretical explanation. It has become clear at this stage that a mere extension of existing theories is not sufficient, but that new approaches have to be taken to establish a more complete understanding of dynamic effects in foams.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin